Examining the automaticity and symmetry of sound–shape correspondences - Chen, Yi-Chuan; Huang, Pi-Chun (Frontiers in Psychology, 2023)
Introduction A classic example of sound–shape correspondences is the mapping of the vowel /i/ with angular patterns and the vowel /u/ with rounded patterns. Such crossmodal correspondences have been reliably reported when tested in explicit matching tasks. Nevertheless, it remains unclear whether such sound–shape correspondences automatically occur and bidirectionally modulate people’s perception. We address this question by adopting the explicit matching task and two implicit tasks. Methods In Experiment 1, we examined the sound–shape correspondences using the implicit association test (IAT), in which the sounds and shapes were both task-relevant, followed by an explicit matching task. In Experiments 2 and 3, we adopted the speeded classification task; when the target was a sound (or shape), a task-irrelevant shape (or sound) that was congruent or incongruent to the target was simultaneously presented. In addition, the participants performed the explicit matching task either before or after the speeded classification task. Results and Discussion The congruency effect was more pronounced in the IAT than in the speeded classification task; in addition, a bin analysis of RTs revealed that the congruency effect took time to develop. These findings suggest that the sound–shape correspondences were not completely automatic. The magnitude and onset of visual and auditory congruency effects were comparable, suggesting that the crossmodal modulations were symmetrical. Taken together, the sound–shape correspondences appeared not to be completely automatic, but their modulation was bidirectionally symmetrical once it occurred.